2005
DOI: 10.1074/jbc.m412898200
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cholesterol Metabolism in Niemann-Pick Type C1 Mouse Brains Affects Mitochondrial Function

Abstract: Niemann-Pick type C1 (NPC1) disease is a fatal hereditary disorder characterized by a defect in cholesterol trafficking and progressive neurodegeneration. Although the NPC1 gene has been identified, the molecular mechanism responsible for neuronal dysfunction in brains of patients with NPC1 disease remains unknown. This study demonstrates that the amount of cholesterol within mitochondria membranes is significantly elevated in NPC1 mouse brains and neural cells. In addition, the mitochondrial membrane potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
186
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(195 citation statements)
references
References 47 publications
9
186
0
Order By: Relevance
“…Proteins were solubilized with CHAPS, separated by size exclusion chromatography, and the elution profile of Bax was analyzed by immunoblotting. For each condition, even-numbered fractions were loaded on two separate gels; a short exposure time was chosen for the low molecular weight fractions (30-44), and a longer one for the high molecular weight fractions (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and its sensitivity to trypsin digestion were analyzed by immunoblotting. The presence of tBid was required for the recruitment of Bax to liposomes and led to the appearance of a Tr-Bax fragment (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins were solubilized with CHAPS, separated by size exclusion chromatography, and the elution profile of Bax was analyzed by immunoblotting. For each condition, even-numbered fractions were loaded on two separate gels; a short exposure time was chosen for the low molecular weight fractions (30-44), and a longer one for the high molecular weight fractions (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and its sensitivity to trypsin digestion were analyzed by immunoblotting. The presence of tBid was required for the recruitment of Bax to liposomes and led to the appearance of a Tr-Bax fragment (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
“…It interferes with the trafficking of cholesterol, causing its increase in late endosomes/lysosomes, 23,24 and inhibits its neosynthesis in the ER. 25 A recent study reported the accumulation of cholesterol in the mitochondria of neurons isolated from an Niemann-Pick Type C1 mouse model, 26 raising the possibility that U18666A might also increase mitochondrial cholesterol content. We therefore incubated HeLa cells with U18666A, isolated mitochondria, and analyzed their lipid composition by thin-layer chromatography (Figure 3a and b).…”
Section: Resultsmentioning
confidence: 99%
“…15) via the modulation of amyloid-␤ synthesis (16,17). Other lines of evidence suggest that cholesterol plays essential roles in the modulation of tau phosphorylation (6,18,19), neurofibrillary tangle formation (20), and neuronal survival (21,22). These lines of evidence suggest that Alzheimer disease pathologies preferentially developing in specific brain regions may be explained by a region-specific difference in the lipid profile.…”
mentioning
confidence: 94%
“…These associations raise the possibility that oxidative stress is a signifi cant factor contributing to the etiology of NPC disease. Indeed, NPCaffected cells exhibit mitochondrial dysfunctions ( 83 ), increased expression of reactive oxygen species (ROS)-producing and oxidative stress-responsive genes ( 84 ), and elevated plasma levels of oxidized cholesterol ( 85 ). Recent studies demonstrated that plasma samples from human NPC patients exhibit compromised ex-vivo antioxidant capacity ( 86 ).…”
Section: Vitamin E Status In Npc-affected Micementioning
confidence: 99%